Chimeric Virus-Like Particles and Capsomeres Induce Similar CD8+ T Cell Responses but Differ in Capacity to Induce CD4+ T Cell Responses and Antibody Responses - Pattinson, David J.; Apte, Simon H.; Wibowo, Nani; Rivera-Hernandez, Tania; Groves, Penny L.; Middelberg, Anton P. J.; Doolan, Denise L. (Frontiers in Immunology, 2020)
Despite extensive research, the development of an effective malaria vaccine remains elusive. The induction of robust and sustained T cell and antibody response by vaccination is an urgent unmet need. Chimeric virus-like particles (VLPs) are a promising vaccine platform. VLPs are composed of multiple subunit capsomeres which can be rapidly produced in a cost-effective manner, but the ability of capsomeres to induce antigen-specific cellular immune responses has not been thoroughly investigated. Accordingly, we have compared chimeric VLPs and their sub-unit capsomeres for capacity to induce CD8+ and CD4+ T cell and antibody responses, and to protect against Plasmodium sp. sporozoite challenge. We produced chimeric murine polyomavirus VLPs and capsomeres each incorporating defined CD8+ T cell, CD4+ T cell or B cell repeat epitopes derived from Plasmodium yoelii CSP. VLPs and capsomeres were evaluated using both homologous or heterologous DNA prime/boost immunization regimens for T cell and antibody immunogenicity. Chimeric VLP and capsomere vaccine platforms induced robust CD8+ T cell responses at similar levels which was enhanced by a heterologous DNA prime. The capsomere platform was, however, more efficient at inducing CD4+ T cell responses and less efficient at inducing antigen-specific antibody responses. Our data suggest that capsomeres, which have significant manufacturing advantages over VLPs, should be considered for diseases where a T cell response is the desired outcome.